Planejamento Estratégico: Análise Fofa Aplicada Na Construção Civil Um Estudo De Caso Na Construtora Mattos - Silva, Kleiverton Luiz Barbosa da (Universidade Federal do Tocantins, 2022)
Strategic planning is essential for the survival of any organization in any field of activity, understanding the environments as a whole helps in decision making and strategy development. The productive process of civil construction is very complex, which requires strategic management and tools that enable the correct execution so that there is no rework in these processes, avoiding losses. In order to have a good strategic planning, it is necessary to know all the scenarios in which the construction company object of this case study is inserted, so that the decision making is effective and accurate. SWOT Analysis is a tool used in administration that helps to understand the environments in which the organization is inserted, both internally and externally, this tool has a capacity to mold and adapt in any situation. In this context, the proposal of this case study is to evaluate the use of the SWOT analysis tool in a construction company in the city of Palmas - TO, evaluating the scenarios and solving the problems after the application of the tool.